Optimalisasi Lab Bahasa Melalui Kelas Multimedia Dalam Program Pengembangan Pengajaran English For Nursing Student - Yani, Mar (LPPM Universitas Bumigora Mataram, 2018)
Mastery of foreign languages, especially English is very important for every people. English is an international whose existence is needed in everything, especially in the world of education. Nursing students were not free from demans of mastering the English language caused many factors. The various needs mastery of English language by nursing students, English teaching materials should be developed and matched with their needs, one of them is to develop multimedia-based material models that used video, audio and image.The method of this research used research and development method. The population of this research were nursing students of STIKES Surya Global Yogyakarta. The technique and collecting data used observation, questioner and interview. Analysis of the data used central terdency measure.From the results obtained that the learning media is very interesting for students and make them motivated to learn more english language. The media can also help their language skills such as listening and speaking especially pronouncation. But there were still deficiencies in the facilities and tools of language laboratoty that inhibits in giving materials, and also the limited time of trial test so that the result of edia development has not been maximized.